Model Kepemimpinan Transformasional dalam Meningkatkan Mutu Pendidikan Islam - Muhammad Yunus Almator; Muhammad Jiddan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Leadership in Islamic educational institutions still faces various challenges, particularly in efforts to improve educational quality sustainably amidst social changes and the continuous advancement of science. These issues indicate the need for a leadership model that is not only oriented toward administrative aspects but also possesses transformative and visionary qualities. This research aims to examine the transformational leadership model and its relationship with enhancing the quality of Islamic education. This study employs a qualitative approach with a literature review method, involving critical analysis of various scientific literatures related to transformational leadership theory and the concept of quality in Islamic education. The results show that the transformational leadership style contributes significantly to the improvement of educational quality. This is achieved through strengthening the institutional vision, empowering human resources, enhancing teacher professionalism, and establishing a productive academic culture in accordance with Islamic values. Therefore, the transformational leadership model is suitable to be implemented as a strategy to systematically and sustainably improve the quality of Islamic education.